2019
DOI: 10.1101/544577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chasing the full free energy landscape of neuroreceptor/ligand unbinding by metadynamics simulations

Abstract: Predicting the complete free energy landscape associated with protein-ligand unbinding would greatly help designing drugs with highly optimized pharmacokinetics.Here we investigate the unbinding of the iperoxo agonist to its target human neuroreceptor M 2 , embedded in a neuronal membrane. By feeding out-of-equilibrium molecular simulations data in a classification analysis, we identify the few essential reaction coordinates of the process. The full landscape is then reconstructed using an exact enhanced sampl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…4). Taken together, these results are consistent with previous WT-MetaD-based free energy calculations which showed excellent agreement between calculated and experimental affinities for this 21,30 and other systems. This is expected and it is indeed confirmed by countless examples, both in protein-ligand 37 and protein-protein 38 interactions.…”
Section: Fa-metadsupporting
confidence: 92%
See 2 more Smart Citations
“…4). Taken together, these results are consistent with previous WT-MetaD-based free energy calculations which showed excellent agreement between calculated and experimental affinities for this 21,30 and other systems. This is expected and it is indeed confirmed by countless examples, both in protein-ligand 37 and protein-protein 38 interactions.…”
Section: Fa-metadsupporting
confidence: 92%
“…We followed the same protocol as in ref. 21 to build and equilibrate the systems and run MD. Briefly, we obtained the structure from the protein data bank (PDB code: 4MQS 45 ), parametrized the ligand using GAFF, 19 and embedded it in a neuronal-like 26 membrane.…”
Section: System Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Computationally, iperoxo dissociation was simulated using metadynamics by Capelli et.al. 30 Two egress routes of iperoxo through the ECV were observed in these simulations with one being predominant. It was suggested that the presence of the PAM would block dissociation by both routes.…”
Section: Introductionmentioning
confidence: 84%
“…It was suggested in Ref. 30 , that a change in the position of ECL2 might enable opening of an additional egress route on the other side of ECL2. Although we do not observe sizeable rearrangements of the ECL2 position, the additional egress route ECV3, as well as displacement of the ECV2 channel, are indeed observed in RAMD simulations of iperoxo in the presence of PAM, as discussed above (see also Fig.…”
Section: Comparison Of Simulations Reveals Ligand Egress Features That Are Sensitive To the Random Force Magnitudementioning
confidence: 99%